Physical activity and well-being group in primary health care: report of an experience of pet-mental health in Porto Alegre - Lidiane Tavares Mielczarski; Franciane Gonçalves Lima; Luciana Balestrin Redivo Drehmer (Universidade de Santa Cruz do Sul, 2012)
KEYWORDS Education and health, Physical activity, Primary care